, DMCN 43: 234–8 (Developmental Medicine and Child Neurology, 2001)
Developmental and/or epileptic encephalopathy with spike-wave activation in sleep is a childhood epileptic encephalopathy spectrum where sleep-related spike-wave discharges drive neurocognitive regression during critical developmental periods. This narrative review synthesizes current evidence on underlying mechanisms and presents an updated diagnostic framework. Impaired slow-wave activity downscaling and sleep spindle disruption predict neurocognitive outcomes more robustly than spike-wave index alone, with thalamic integrity emerging as an independent prognostic marker. Genetic diagnoses have been identified in up to 55% of cases, with GRIN2A variants the most common monogenic aetiology. A structured review of published articles detailing 293 individuals confirmed that language, cognitive, and behavioural impairments frequently coincided with, or sometimes occurred independently of, seizure onset. Our proposed diagnostic framework integrates sleep electroencephalogram-prioritizing spindle preservation and slow-wave organization-alongside high-resolution magnetic resonance imaging, trio-based genomic sequencing, and longitudinal neuropsychological assessment. Further research is needed to validate sleep-based biomarkers and determine whether early intervention improves neurodevelopmental outcomes.